Acoustic performance in a lightweight ventilated façade for building refurbishment:: analysing the impact of variations in airborne sound insulation according to the ventilation characteristics - Niampira Daza, Andrea; Zamora, Joan Lluís (Revista de la Construcción. Journal of Construction, 2019)
The use of double-sheet enclosures with an intermediate air chamber in façades guarantees a higher quality of acoustic insulation against external airborne noise. The effective advantages of the intermediate air chamber depend mainly on its airtightness and the absorbent material contained inside. A ventilated façade with lightweight cladding (LVF) is a specific construction system for double-sheet envelope façades, characterised by an intermediate air chamber that enables a certain amount of internal air circulation, with resulting cooling effects to alleviate excess solar radiation whilst reducing the risk of dampness caused by rainwater. However, owing to this ventilation of the intermediate air chamber, the acoustic insulation of the entire façade could prove less effective than cases in which the intermediate air chamber is completely sealed. Through various methods of measurement and analysis, several authors consider that the opening of the intermediate air chamber for hygrothermal control purposes does not necessarily represent a significant reduction in the level of sound insulation in general. What does appear to have a significant influence on the acoustic behaviour is the surface and location of the intermediate air chamber openings to enable ventilation. The results of this research are presented as further evidence that the positive contribution of LVF should be acknowledged at a regulatory level regarding sound insulating, double-sheet envelope architectural façades.